The Legal Policy of Regional Autonomy from the Perspectives of Constitutional Law and Ushul Fiqh - Dede Ika Murofikoh; Fitri Dian AL Aufa; Restu Gusti Monitasari (Rechtsvinding, 2026)
This article analyzes the legal politics related to regional autonomy from the perspectives of Constitutional Law and Usul Fiqh. The study of Usul Fiqh provides an ethical and normative basis that emphasizes that every policy of power must be directed toward the benefit of society and the prevention of harm. The integration of these two perspectives is important so that regional autonomy policies are not only legally valid but also just and socially beneficial. This study aims to analyze the legal politics of regional autonomy from the perspectives of Constitutional Law and Usul Fiqh, in order to identify the normative basis, principles of benefit, and their relevance to the dynamics of changing times. This research employs a normative approach using literature reviews, examining the legal politics of regional autonomy through journals, books, and other sources related to Constitutional Law and Usul Fiqh for analysis. This study reveals that regional autonomy is a concept that grants authority to regional governments to regulate and manage governmental affairs and community interests within their regions, in accordance with the principle of decentralization. This concept aims to accelerate regional development, improve public services, and provide opportunities for regions to develop in accordance with their existing local potential. The decentralization of authority to regions enables more effective public services, policies that are more responsive to local needs, equitable development, and strengthened community participation. Thus, regional autonomy can be categorized as a mursalah issue—a benefit not explicitly stated in the texts but consistent with the general objectives of Sharia